NILAI-NILAI DAKWAH ISLAMIAH, POLITIK DAN TOLERANSI DALAM PIAGAM JAKARTA - PUTRI KRISDIANA (Mudabbir: Jurnal Manajemen Dakwah, 2021)
This paper examines the influence of Islamic values, politics and tolerance in the Jakarta Charter. The two main discussions answered in this article are how the struggle for Islamic da'wah values, politics and tolerance in the Jakarta Charter has an impact on the value of religious tolerance in Indonesia. In answering these two main problems, this paper uses paratext theory as an analytical tool. The main data used in this article consist of books, journals, catalogs, scientific papers, websites, theses, theses and dissertations. From the search results, the author finds that the Jakarta Charter has undergone various changes, such as the deletion of seven words. This was solely intended so that the Protestant and Catholic groups would not separate themselves from the Republic of Indonesia. So Muslims are willing to sacrifice these seven meaningful words. The decisions taken by several Islamic leaders in a very short time really reflect the moderate attitude of Islamic da'wah and a good attitude for religious tolerance in the Republic of Indonesia.